Mer de Barents, côtes de la Norvège, de la Finlande et de l'U.R.S.S., du Cap Nord au Cap Tcherni / d'après les levés norvégiens et russes les plus récents Service hydrographique de la marine . 1940 (1947)
Publication provisoire. Corr. . 1947 Relief shown by spot heights and hachures. Depths shown by bathymetric isolines and soundings.; Selected lights shown in orange.; Pasteover at Presqu'île Sredni Color; 1:530,400